Successful Surgical Management of Haemodynamically Evaluated Uterine Torsion in a Bitch - Bhathra, N R; Gupta, Chhavi; V, Prabaharan; A, Ganesan; A, Sabarinathan (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Uterine torsion is defined as the twisting of the uterus or uterine horn perpendicular to its long axis and is more  commonly observed in multiparous animals (Thilagar et al.,  2011). Predisposing factors for uterine torsion are excessive  fetal movements, lack of fetal fluids, premature uterine  contractions, usage of ecbolic therapy, hereditary weakness  of uterine ligament, hyperactivity of the pregnant animal like  jumping, rolling, running in late gestation period etc (Gupta  et al., 2020). The clinical signs and haemodynamic changes  of the middle uterine artery are directly proportional to the  torsion degree, which can vary between 180° and 90° both  clockwise and counter clockwise, hence, these parameters  are considered as prognostic indicators (Thilagar et al.,  2011). Doppler ultrasound evaluation of uterine blood flow  is a non-invasive technique for early diagnosis of uterine  torsion in canines. Further, velocimetric indices could be  useful to differentiate the side of torsion (Sudha et al., 2019).  This document represents successful surgical management  of haemodynamically evaluated uterine torsion in a bitch.
Keywords: hyperechoic fetal; skeleton; Uterine torsion